Effect of solution heat treatment on microstructure and mechanical properties of laser powder bed fusion produced cobalt-28chromium-6molybdenum - Sing, Swee Leong (2020)
Cobalt-chromium-molybdenum (CoCrMo) alloys have excellent properties that make them widely used in dental applications. Selective laser melting (SLM) is a laser powder bed fusion (L-PBF) additive manufacturing (AM), or 3D printing, technique that can fabricate functional parts directly using these alloys. In this work, SLM is used to fabricate CoCrMo samples and they underwent different heat treatments originally designed for casted CoCrMo alloy. The mechanical properties, such as ultimate tensile strength, yield strength and microhardness of the heat treated SLM CoCrMo parts are evaluated and benchmarked against their casted counterparts. It is found that as-built samples have anisotropy properties while heat treated samples displayed isotropic properties. As-built SLM CoCrMo specimens demonstrated approximately twice the yield strength (YS) and ultimate tensile strength (UTS) as compared to ASTM F75 standard for cast CoCrMo alloys. However, both UTS and YS of SLM CoCrMo decreased after heat treatment. The microstructure analysis concluded carbides formation because of the heat treatments.